Electrocardiography in conscious releasable Andean Condors (Vultur gryphus): reference panel and unusual findings - Wiemeyer, Guillermo M. (2013)
Electrocardiography is a useful tool when included in healthcare protocols and is increasingly utilized for monitoring wild birds. However, the lack of reference data for many species is limiting its clinical value of this technique. In this study twenty-six Andean condors (Vultur gryphus) coming from rehabilitation and captive breeding programs were examined to determine electrocardiographic references prior to being released. Standard bipolar (I, II and III) and augmented unipolar limb (aVR, aVL and aVF) leads were recorded with birds under physical restraint. Five beats were analyzed on Lead II at 50 mm/sec and 1 cm = 1 mV to determine QRS complex morphology, cardiac rhythm, heart rate, P, PR, R, S, QRS, T, QT and ST amplitude and/or duration. P and T wave configuration was determined for all leads, and Mean Electrical Axis (MEA) in the frontal plane was determined using leads I and III. Cardiac rhythm corresponded to regular sinus rhythm in 42% of the birds, with a relevant rate of sinus arrhythmia in 58%, and rS as the most common pattern (42%) for QRS complex in lead II. We found an influence of age and heart rate but not of sex on several ECG waves and intervals. Relevant ECG findings for studied Andean condors include a high rate of Ta, R´ and U wave detection. Waves Ta and R´ were considered non pathological, while the significance of U waves remains unclear. Our results provide a useful reference to improve clinical interpretation of full electrocardiographic examination in Andean condors.